2019
DOI: 10.20307/nps.2019.25.4.311
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effect of Flavonoids fromArtocarpus heterophyllusHeartwoods on Anticancer Activity of Cisplatin Against H460 and MCF-7 Cell Lines

Abstract: Artocarpus heterophyllus has been used as traditional medicine. This plant is one of the sources of flavonoid. Flavonoid compounds possessed a wide range of biological properties including anticancer. This study was performed to investigate the cytotoxic effect of flavonoids from A. heterophyllus on H460 and MCF-7 cell lines. The interaction of flavonoids and cisplatin against tested cancer cells was also evaluated. MTT assay was used to determine the cytotoxic effect of flavonoid. Isobologram analysis was sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 27 publications
2
4
0
Order By: Relevance
“…This result further supports the previous findings on the anticancer activity of this compound on various cancer cell lines, including human leukaemia HL-60 (CCL-240) cells, colorectal adenocarcinoma HT-29 (HTB38) cells, breast adenocarcinoma cancer MCF-7 (HTB-22) cell, and non-small lung cancer H460 (HTB-177) cell lines (Daud et al, 2019;Mat Daud et al, 2021). Furthermore, in H460, artocarpin displayed antiproliferation, antidifferentiation, antimigration, and anti-invasion capabilities (Daud et al, 2020).…”
Section: Discussionsupporting
confidence: 91%
“…This result further supports the previous findings on the anticancer activity of this compound on various cancer cell lines, including human leukaemia HL-60 (CCL-240) cells, colorectal adenocarcinoma HT-29 (HTB38) cells, breast adenocarcinoma cancer MCF-7 (HTB-22) cell, and non-small lung cancer H460 (HTB-177) cell lines (Daud et al, 2019;Mat Daud et al, 2021). Furthermore, in H460, artocarpin displayed antiproliferation, antidifferentiation, antimigration, and anti-invasion capabilities (Daud et al, 2020).…”
Section: Discussionsupporting
confidence: 91%
“…This result further supports the previous findings on the anticancer activity of this compound on various cancer cell lines, including human leukaemia HL-60 (CCL-240) cells, colorectal adenocarcinoma HT-29 (HTB38) cells, breast adenocarcinoma cancer MCF-7 (HTB-22) cell, and non-small lung cancer H460 (HTB-177) cell lines (Daud et al, 2019;Mat Daud et al, 2021). Furthermore, in H460, artocarpin displayed antiproliferation, antidifferentiation, antimigration, and anti-invasion capabilities (Daud et al, 2020).…”
Section: Discussionsupporting
confidence: 91%
“…The mechanism of flavonoid's action in potentiating cisplatin treatment is depletion of the cellular oxidative machinery, aiding mitochondrial dysfunction and thus leading to apoptosis [144]. A few more examples of flavonoids, such as artocarpanone, artocarpin, cycloartocarpin, and cyanomaclurin, extracted from Artocarpus heterophyllus heartwoods have a synergistic effect with cisplatin on non-small lung and breast cancers [145]. Recent studies have shown that quercetin prevented cisplatin nephrotoxicity by ameliorating tubular damage [146].…”
Section: Combination With Flavonoidsmentioning
confidence: 99%